EFFECT OF TEMPERATURE AND EXTRACTION TIME ON YIELD, MOISTURE CONTENT, AND COCONUT COIR METHOXYL PECTIN - Mamuaja, Christine F; Lumuindong , Frans (ITScience (Information Technology and Science), 2023)
This study aims to see the effect of temperature and extraction time on moisture content, yield and methoxyl pectin content of coconut coir. This research was conducted with a factorial experiment in a completely randomized design (CRD), which consisted of two treatments, namely extraction temperature and extraction time with three replications. The results of this study indicate that the extraction temperature greatly affects the pectin yield, water content and methoxyl pectin while the extraction time affects the pectin water content. At a temperature of 70OC and an extraction time of 60 minutes, the highest average yield of pectin was obtained, namely 4.31%, while the lowest average yield of pectin was obtained from the treatment of an extraction temperature of 90OC and an extraction time of 90 minutes. The highest average methoxyl content was obtained from a temperature treatment of 70OC and an extraction time of 30 minutes, while the lowest average percentage of methoxyl content was obtained from a temperature treatment of 90OC extraction and an extraction time of 90 minutes, namely 8.03% and 7.61%, respectively. From the results obtained, it was concluded that the pectin obtained belonged to the pectin group with high methoxyl content, namely >7%. The lowest average percentage of pectin content was obtained at 90OC and 90 minutes of extraction time, namely 10.19%, while the highest was obtained from the treatment of 70OC extraction temperature and 30 minutes of extraction time. From the results of the analysis of water content, it was found that the water content of cocopeat pectin obtained in this study fulfilled the requirements for dry pectin moisture content, namely 10-14%.